Dari Mimbar ke Misi Peran Pemimpin Kristen dalam Penginjilan Pribadi di Gereja Bethel Indonesia - Sahabat Sebayang; Andreas Eko Nugroho; Rulli Jonathans (Sekolah Tinggi Teologi Berita Hidup, 2025)
This study discusses the role of Christian leadership and personal evangelism in completing the great commission. Christian leadership is a leader who is called by God, to carry out the task of God's calling based on the Bible as a guideline in his leadership. The researcher used a qualitative method or literature review to research this article. Spiritual growth in terms of quality and quantity of the congregation in Christianity, cannot be separated from Christian leadership and personal evangelism that carry out the mandate of the great commission. However, in the journey of completing the mission of the great commission, there are still several things that need to be implemented by Christian leaders and personal evangelisms for the creation of each individual to meet authentically with the teachings of the Lord Jesus, especially during the harvest at the end of time. The purpose of this study is to answer the research question of how the implementation of the completion of the great commission in the mission of Christian leaders and personal evangelism and its implications in the environment of the Bethel Church of Indonesia. The conclusion in this study, Christian leadership plays an important role in the participation of GBI congregations in personal evangelism. With a holistic approach, inhibiting factors such as lack of training and fear of rejection can be overcome. On the other hand, supporting factors such as community support and leader examples must be strengthened. By optimizing leadership strategies and personal evangelism, GBI can be more effective in completing the Great Commission and making all nations disciples of Christ. enelitian ini membahas tentang peranan kepemimpinan Kristen dan penginjilan pribadi dalam menuntaskan amanat agung. Kepemimpinan Kristen adalah pemimpin yang dipanggil oleh Allah, untuk menjalankan tugas panggilan Allah berdasarkan Alkitab sebagai pedoman dalam kepemimpinannya. Peneliti menggunakan metode kualitatif atau kajian pustaka untuk meneliti artikel ini. Pertumbuhan rohani secara kualitas dan kuantitas jemaat dalam kekristenan, tidak terlepas dari kepemimpinan Kristen dan penginjilan pribadi yang melakukan mandat amanat agung. Namun dalam perjalanan penuntasan misi amanat agung ini, masih terdapat beberapa hal yang perlu diimplementasikan oleh para pemimpin Kristen dan penginjil pribadi bagi terciptanya setiap individu bertemu secara autentik dengan ajaran Tuhan Yesus terutama dimasa penuaian diakhir zaman. Tujuan dari penelitian ini adalah menjawab pertanyaan penelitian bagaimana implementasi dari penuntasan amanat agung dalam misi pemimpin Kristen dan penginjilan pribadi serta implikasinya dilingkungan Gereja Bethel Indonesia. Kesimpulan dalam penelitian ini, kepemimpinan Kristen memegang peranan penting untuk partisipasi jemaat GBI dalam penginjilan pribadi. Dengan pendekatan holistik, faktor penghambat seperti kurangnya pelatihan dan ketakutan akan penolakan dapat diatasi. Dilain pihak, faktor pendukung seperti dukungan komunitas dan teladan pemimpin harus diperkuat. Dengan mengoptimalkan strategi kepemimpinan dan penginjilan pribadi, GBI dapat lebih efektif dalam menuntaskan Amanat Agung dan menjadikan semua bangsa murid Kristus.